RE-INVENSI BATIK DAN IDENTITAS INDONESIA DALAM ARENA PASAR GLOBAL - Moersid, Ananda Feria (Jurnal Ilmiah Widya, 2013)
Re-Invention of Batik and Indonesian Identity in the Global Market Arena. Nowadays, what is called ‘tradition’ that appears to be or declared to be ‘old’ often has a recent or new origin or even constitutes a new re-invention. Re-invention is a conscious effort to construct a new identity based on tradition as a builder of social ties and politically legitimize status and authority. If the so called ‘authentic’ tradition can also be constructed or reconstructed for political or for the sake of tourism, the question is how we position traditional visual arts, in this case batik within the global market. How do we render our qualities into marketable commodity, fit for competition on the global market. Economic capital is not enough; efforts must be made to attain cultural capital, a constant cultural knowledge, competence and superiority in one’s field. Only by the ability to change, form and condition batik as a cultural production, the re-invention of tradition becomes our source of creativity and our identity in the global arena.